Pelaksanaan Pengawasan Penyelenggaraan Reklame di Kota Semarang oleh Dinas Penataan Ruang Kota Semarang terhadap Lingkungan - M. Islahul Rizky; Waluyo Waluyo; Fatma Ulfatun Najicha (Faculty of Law Universitas Sebelas Maret Surakarta, 2022)
This study aims to reveal and analyze the implementation of supervision of billboard organizers in Semarang City by the Spatial Planning Office of Semarang City and analyze the efforts made by the Government of Semarang City in order to improve order in Semarang City. The type of research conducted by the author is empirical legal writing. The results of field data and interviews, the implementation of supervision of the implementation of billboards in the City of Semarang by the Spatial Planning Service is not perfect from its implementation in the field based on Regional Regulation Number 4 of 2019 concerning Billboards, then seen from the obstacles in carrying out supervision of billboard organizers and view from the Semarang City environment , which resulted in delays in the implementation of the supervision, so that the implementation is not perfect.